Immobilization of Functionalized epi-Cinchonine Organocatalysts on Controlled Porous Glass Beads: Applications in Batch and Continuous Flow - Amorim, Ana C.; Fonseca, Daniela P.; Carreiro, Elisabete P.; Hermann, Gesine J.; Federsel, Hans-Jürgen; Burke, Anthony J. (Synlett, 2022)
A well-known squaramide-cinchonine organocatalyst was immobilized in a controlled way onto three types of commercial porous glass beads EziG™ (EziG OPAL, EziG Amber, and EziG Coral) and applied in asymmetric Michael reactions. The performance of the immobilized catalysts was evaluated under batch and continuous-flow conditions, showing promising results in both approaches. In batch reactions, 0.8 and 1.6 mol% of the immobilized cinchonine-squaramide provided the products with excellent yields (up to 99%) and enantioselectivities (up to 99% ee). These excellent results were also verified in the case of continuous-flow reactions, where also 0.8 and 1.6 mol% of the catalyst immobilized onto the glass beads afforded the product with extraordinary yields (up to 99%) and very high enantioselectivities (up to 97% ee). The immobilized catalysts could be recycled (up to seven cycles) using both approaches.
Keywords: cinchona alkaloids; EziGTM; immobilizations; batch reactions; continuous flow reactions; organocatalysis